Accounting Edutainment an Alternative Accounting Learning (Dictionary and Accounting terms) - Sanriomi Sintaro (Jurnal Ilmiah Sistem Informasi Akuntansi, 2023)
In the world of accounting education, there is a perception that accounting subject is difficult to learn, in public high school, accounting subjects are categorized as difficult with presentations above 65 percent of students saying that accounting is a difficult subject to understand. To improve student motivation to get better learning material for this subject, parents and teacher must using effective, efficient, and interesting accounting learning yet also give motivation to the student. We can do that by using edutainment. It is intended that edutainment in accounting learning can later be used as a new, more interesting learning material, the material chosen in this study is about accounting terms which can be used as a basis for future accounting learning. The conclusion is that the Accounting Edutainment Dictionary and Accounting terms can work well by providing accounting terms to users, by using blackbox testing it can be proven that the Accounting Edutainment Dictionary and Accounting terms can be run without significant problems. Then the test was carried out on 413 respondents using ISO 25010 to produce a value from the functionality aspect with very good results, namely with a presentation of 82.2%, from the efficiency aspect with very good results, namely with a presentation of 84.3%, from the usability aspect with very good results, namely with a presentation by 80.6%. Then from the results of the PIECES analysis, it can be concluded that the scenes in edutainment can provide easy information to its users.